2019
DOI: 10.1080/02673037.2019.1648770
|View full text |Cite
|
Sign up to set email alerts
|

Hybridity in the housing sector: examining impacts on social and private rented sector tenants in Scotland

Abstract: Housing Associations in many countries exhibit increasing levels of 'hybridity', as reductions in state financing for social housing, exacerbated by austerity policies since the 2008 crash, have instigated 'enterprising' approaches to maintaining income. Alongside this, hybrid organisations have emerged in the Private Rented Sector (PRS), responding to sectoral growth and consequent increases in vulnerable households entering private renting. These developing hybridities have been considered at a strategic lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The following study is part of the CommonHealth (see https://www.commonhealth.uk/ ) research programme, which aimed to develop methods to evaluate new pathways to health creation and health inequalities reduction arising from community-based social enterprises. CommonHealth comprised of eight projects focussing on specific social needs/contexts including young people, rural communities ( Kelly et al , 2019a ), homelessness ( Rolfe et al , 2019 ) and marginalized women ( Hill O’Connor et al , 2018 ). The study underpinning this paper considered social enterprises that support older people.…”
Section: Introductionmentioning
confidence: 99%
“…The following study is part of the CommonHealth (see https://www.commonhealth.uk/ ) research programme, which aimed to develop methods to evaluate new pathways to health creation and health inequalities reduction arising from community-based social enterprises. CommonHealth comprised of eight projects focussing on specific social needs/contexts including young people, rural communities ( Kelly et al , 2019a ), homelessness ( Rolfe et al , 2019 ) and marginalized women ( Hill O’Connor et al , 2018 ). The study underpinning this paper considered social enterprises that support older people.…”
Section: Introductionmentioning
confidence: 99%
“…Tenants of the 'hybrid' housing organisation (Rolfe et al, 2019) organised as a social enterprise showed relatively greater health and wellbeing improvements and satisfaction with their letting agency compared to the Housing Association and private landlord tenants. Considering the implications of these findings, therefore, social enterprises may have a significant role to play in relieving pressure on social housing and providing better outcomes for vulnerable tenants compared with the mainstream, for-profit sector.…”
Section: Project 7: Housing Through Social Enterprisementioning
confidence: 97%
“…The notion of 'hybridity' is often used to describe the organisational changes that have arisen as traditional public or community (not-for-profit) housing providers have shifted towards more quasi commercial practices to secure additional funding and expand or cross subsidise their operations (Blessing 2012;Mullins, Milligan et al 2018). There is a large and growing literature on the implications of this 'state directed' hybridity in the formerly not-for-profit housing sector (Mullins, Milligan et al 2018;Rolfe, Garnham et al 2020).…”
Section: Hybridity In Social and Affordable Housing Provisionmentioning
confidence: 99%